FGFR‐associated craniosynostosis syndromes and gastrointestinal defects. Issue 12 (2nd August 2016) - Hibberd, Christine E.; Bowdin, Sarah; Arudchelvan, Yamini; Forrest, Christopher R.; Brakora, Katherine A.; Marcucio, Ralph S.; Gong, Siew‐Ging
Abstract : Craniosynostosis is a relatively common birth defect characterized by the premature fusion of one or more cranial sutures. Examples of craniosynostosis syndromes include Crouzon (CS), Pfeiffer (PS), and Apert (AS) syndrome, with clinical characteristics such as midface hypoplasia, hypertelorism, and in some cases, limb defects. Mutations in Fibroblast Growth Factor Receptor‐2 comprise the majority of known mutations in syndromic forms of craniosynostosis. A number of clinical reports of FGFR‐ associated craniosynostosis patients and mouse mutants have been linked to gastrointestinal tract (GIT) disorders, leading to the hypothesis of a direct link between FGFR‐ associated craniosynostosis syndromes and GIT malformations. We conducted an investigation to determine GIT symptoms in a sample of FGFR‐ associated craniosynostosis syndrome patients and a mouse model of CS containing a mutation (W290R) in Fgfr2 . We found that, compared to the general population, the incidence of intestinal/bowel malrotation (IM) was present at a higher level in our sample population of patients with FGFR ‐associated craniosynostosis syndromes. We also showed that the mouse model of CS had an increased incidence of cecal displacement, suggestive of IM. These findings suggest a direct relationship between FGFR ‐related craniosynostosis syndromes and GIT malformations. Our study may shed further light on the potential widespread impact FGFR mutations on different developmental systems. Based on reports of GIT malformations in children with craniosynostosis syndromes and substantiation with our animal model, GIT malformations should be considered in any child with an FGFR2 ‐associated craniosynostosis syndrome. © 2016 Wiley Periodicals, Inc.